2011
DOI: 10.1002/jcp.22579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of membrane cholesterol depletion and GPI‐anchored protein reduction on osteoblastic mechanotransduction

Abstract: We previously demonstrated that oscillatory fluid flow activates MC3T3-E1 osteoblastic cell calcium signaling pathways via a mechanism involving ATP releases and P2Y 2 puringeric receptors. However, the molecular mechanisms by which fluid flow initiates cellular responses are still unclear. Accumulating evidence suggests that lipid rafts, one of the important membrane structural components, may play an important role in transducing extracellular fluid shear stress to intracellular responses. Due to the limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Our data showed that reduced expression of G␣ q/11 or PLC inhibition consistently increased the time to peak calcium transients by 11 s, but the peak value was only slightly attenuated. Similar increased lags in calcium response were observed in bone cells treated with lipid raft-disrupting agent (41). Interestingly, Kou and colleagues (20) observed a 10-s increase in response time when lowering oscillatory shear stress in osteoblasts.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our data showed that reduced expression of G␣ q/11 or PLC inhibition consistently increased the time to peak calcium transients by 11 s, but the peak value was only slightly attenuated. Similar increased lags in calcium response were observed in bone cells treated with lipid raft-disrupting agent (41). Interestingly, Kou and colleagues (20) observed a 10-s increase in response time when lowering oscillatory shear stress in osteoblasts.…”
Section: Discussionsupporting
confidence: 50%
“…Latency in building up calcium responses was first described to occur within 1 min of shear stress on bovine ECs (3), in which IP 3 was found to precede and peak after 20 -30 s of flow in human umbilical vein endothelial cells (4,27). In more recent studies, a significant lag between the onset of fluid-flow and [Ca 2ϩ ] i increase was also observed in intercalated, renal, and bone cells subjected to shear stress (20,22,33,34,41). Although likely to be a function of the nature of the force applied, this lag time differs between cell types, but the peak occurrence was typically found to be between 10 and 30 s after stimulus.…”
Section: Discussionmentioning
confidence: 95%
“…Altogether, these findings suggest that microdomains could "engulf" fi ssion-associated molecules and associate with mutated Htt, giving rise to a multimolecular complex affecting mitochondrial fate. In addition, however, we cannot rule out the possibility that this association inhibitor ( 29,30 ), and MBC, a raft disruptor ( 13,31 ). Both of these agents are capable of impairing the peculiar mitochondrial remodeling occurring in cells from HD patients, i.e., redistribution and aggregation as well as MMP changes.…”
Section: Discussionmentioning
confidence: 92%
“…With this aim, two different agents capable of perturbating microdomain integrity have been considered: FB1, a ceramide synthase inhibitor ( 29,30 ), and MBC, a raft disruptor ( 13,31 ). We found that either FB1 or MBC, when administered before STS treatment, were capable of signifi cantly hindering apoptosis in HS as well as in HD cells ( Fig.…”
Section: Mitochondrial Raft-like Microdomains and Apoptotic Susceptibmentioning
confidence: 95%
“…When a force is transmitted across the membrane and/or cytoskeleton, the proteins anchored within the lipid rafts sense the force and transduce the signal into the cell. In an initial study evidence was found that GPI-anchored proteins within lipid rafts were involved in converting fluid flow induced shear stress into intracellular responses (primarily Ca 2+ signaling) in osteoblastic cell mechanotransduction [94].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%